Ameliorative Activity of Ethanol Extract of Stem Bark on Pancreatic β-Cell Dysfunction in Alloxan-Induced Diabetic Rats - Basiru O. Ajiboye PhD; Oluwafemi A. Ojo MSc; Oluwatosin Adeyonu BSc; Oluwatosin D. Imiere BSc; Adewale O. Fadaka MSc; Adetutu O. Osukoya PhD (SAGE Publishing, 2017)
This study sought to investigate the ameliorative effects of ethanol extract Artocarpus heterophyllus (EAH) in alloxan-induced diabetic rats. The rats were divided into 6 groups, with groups 1 and 2 serving as nondiabetic and diabetic control, respectively; group 3 serving as diabetic rats treated with 5 mg/kg glibenclamide; and groups 4 to 6 were diabetic rats treated with 50, 100, and 150 mg/kg of EAH, respectively. Assays determined were serum insulin, lipid peroxidation, and antioxidant enzyme activities. EAH stem bark reduced fasting blood glucose and lipid peroxidation levels and increased serum insulin levels and activities of antioxidant enzymes. Data obtained demonstrated the ability of EAH stem bark to ameliorate pancreatic β-cell dysfunction in alloxan-induced diabetic rats.